Kazimierza Wierzyńskiego przygody z przekładami - Osiński, Jakub (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article consists of two parts. In the first part the author refers to seven poems (by Richard Dehmel, Maria Stona, Johannes Schlaf, Aleksander Blok, Taras Szewczenko and Carl Sandburg) translated by Kazimierz Wierzyński and he tries to find the place for them in all of the poet’s writings. The second part of this text is devoted to the most important translations of texts originally written by Wierzyński (poems, prose, drama, biography The Life and Dead of Chopin) in chronological perspective.
Kazimierz Wierzyński’s Experiences with Translations
Keywords: Kazimierz Wierzyński (1894–1969); translation; Polish émigré literature after The Second World War; przekład; literatura emigracyjna